2003
DOI: 10.1093/jn/133.9.2820
|View full text |Cite
|
Sign up to set email alerts
|

Taurine Supplementation of a Low Protein Diet Fed to Rat Dams Normalizes the Vascularization of the Fetal Endocrine Pancreas

Abstract: In rats, an isoenergetic low protein diet (LP) given throughout gestation perturbs the development of the endocrine pancreas by reducing beta-cell mass and islet vascularization at birth. Taurine, an important amino acid during development, has been found to be low in fetal and maternal plasma. When added to a LP diet, taurine normalizes beta-cell mass. Therefore, we investigated the ability of taurine to correct altered islet vascularization. Rats were given 20% [control (C)] or 8% (LP) protein in the diet wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
86
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(95 citation statements)
references
References 37 publications
5
86
2
Order By: Relevance
“…The effect of taurine could result from the fact that taurine administration in fetal and early life led to the development of different beta cell populations in the two groups (CT and RT). We have indeed shown that taurine restored fetal islet vascularisation altered by an LP diet, as well as expression of IGF-2 and vascular endothelial growth factor [5,24]. Vascularisation and vascular endothelial growth factor are of prime importance for the differentiation of the endocrine pancreas [31], and IGFs, being mitogenic and survival factors, modulate the mass of islet cells [6,32].…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…The effect of taurine could result from the fact that taurine administration in fetal and early life led to the development of different beta cell populations in the two groups (CT and RT). We have indeed shown that taurine restored fetal islet vascularisation altered by an LP diet, as well as expression of IGF-2 and vascular endothelial growth factor [5,24]. Vascularisation and vascular endothelial growth factor are of prime importance for the differentiation of the endocrine pancreas [31], and IGFs, being mitogenic and survival factors, modulate the mass of islet cells [6,32].…”
Section: Discussionmentioning
confidence: 63%
“…Moreover, Fas (CD95/APO-1)-mediated neutrophil apoptosis is reported to be inhibited by taurine through calcium homeostasis [22]. Finally, the substance appears to be important for the normal development of the endocrine pancreas, since supplementing a maternal LP diet with taurine has been found to restore a normal taurine concentration in fetal plasma, a normal beta cell mass and a normal insulin secretion by fetal islets [5,23,24]. In vivo and in vitro, taurine prevents the damage to fetal beta cells induced by IL-1β and NO · [7].…”
Section: Introductionmentioning
confidence: 99%
“…We have previously shown that maternal taurine supplementation of the LP diet preserved the normal fetal beta cell phenotype [11,12,15,18,19]. No single gene or specific pathways responsible for the taurine effect could be identified, since every gene had an expression level similar to that in control islets.…”
Section: Discussionmentioning
confidence: 99%
“…Reduction of food intake by 50% in rats during gestation reduced the beta cell mass in offspring at birth by 30% [9]. When maternal diet was reduced in protein content during gestation, a number of findings were observed: reduction in beta cell mass due to diminished proliferation [8,13], enhanced apoptosis [11,13], reduced insulin secretion in vitro from isolated islets [14], impaired islet vascularisation [8,15] and enhanced sensitivity to cytotoxic effects of cytokines in vitro [11]. Increased susceptibility to cytokine cytotoxicity and lower insulin secretion persisted in adulthood despite limiting the low-protein (LP) diet to the period of gestation and lactation [7,12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation